Development of a new HPLC method for wogonin in rat plasma: Compatibility of standard and test samples - Salmani Jumah Masoud Mohammad; Wu Xue; Jacob Joe Antony; Fu Rong; Chen Baoan (Acta Pharmaceutica)
In the current paper, an HPLC/UV method was developed and validated for determination of wogonin in plasma. Considerable attention was paid to the preparation of standard samples and factors affecting drug distribution. A preparation procedure was devised to simulate the conditions the drug is expected to experience in vivo while pointing to the shortcomings of previously published methods. The method was validated according to the FDA regulations and showed to be highly efficient and capable of extracting the drug and IS from the plasma accurately and precisely within the specified range of 50–500 ng mL−1. Further, the standard sample preparation of this method can be used as a guideline for other methods, particularly when highly hydrophobic drugs with considerable protein binding are involved and could be valuable in the field of bioanalysis to improve the reliability of methods.